The effect of Lucilia sericata- and Sarconesiopsis magellanica-derived larval therapy on Leishmania panamensis (2016)
This study's main objective was to evaluate the action of larval therapy derived from Lucilia sericata and Sarconesiopsis magellanica (blowflies) regarding Leishmania panamensis using an in vivo model. Eighteen golden hamsters (Mesocricetus auratus) were used; they were divided into 6 groups. The first three groups consisted of 4 animals each; these, in turn, were internally distributed into subgroups consisting of 2 hamsters to be used separately in treatments derived from each blowfly species. Group 1 was used in treating leishmanial lesions with larval therapy (LT), whilst the other two groups were used for evaluating the used of larval excretions and secretions (ES) after the ulcers had formed (group 2) and before they appeared (group 3). The three remaining groups (4, 5 and 6), consisting of two animals, were used as controls in the experiments. Biopsies were taken for histopathological and molecular analysis before, during and after the treatments; biopsies and smears were taken for assessing parasite presence and bacterial co-infection. LT and larval ES proved effective in treating the ulcers caused by the parasite. There were no statistically significant differences between the blowfly species regarding the ulcer cicatrisation parameters. There were granulomas in samples taken from lesions at the end of the treatments. The antibacterial action of larval treatment regarding co-infection in lesions caused by the parasite was also verified. These results potentially validate effective LT treatment against cutaneous leishmaniasis aimed at using it with humans in the future. © 2016 Elsevier B.V.